2021
DOI: 10.5114/biolsport.2021.106147
|View full text |Cite
|
Sign up to set email alerts
|

Repercussions of the COVID-19 pandemic on athletes: a cross-sectional study

Abstract: The COVID-19 pandemic has presented significant challenges and implications for the sports community. Thus, this study aimed to describe the prevalence of COVID-19 in Brazilian athletes and identify the epidemiological, clinical, athletic, life and health factors associated with the disease in these individuals. A cross-sectional study was performed involving 414 athletes from 22 different sports using an online questionnaire from August to November 2020. The association between the athletes’ characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…The infection rate among professional soccer players is consistent with that of the general population 4 , and most of the time, COVID-19 positive athletes are asymptomatic 6 . However, they may experience mild to moderate symptoms such as fever, cough, loss of taste or smell, headache, aches, muscle pain, sore throat, and tiredness 4 6 . Less common and more severe symptoms include shortness of breath, pain and pressure in the chest, or pneumonia 5 .…”
Section: Introductionsupporting
confidence: 68%
“…The infection rate among professional soccer players is consistent with that of the general population 4 , and most of the time, COVID-19 positive athletes are asymptomatic 6 . However, they may experience mild to moderate symptoms such as fever, cough, loss of taste or smell, headache, aches, muscle pain, sore throat, and tiredness 4 6 . Less common and more severe symptoms include shortness of breath, pain and pressure in the chest, or pneumonia 5 .…”
Section: Introductionsupporting
confidence: 68%
“…Of the 43 studies and 11 518 infected athletes included in this systematic review, the median number (IQR) of participants per study was 26 (15–101). The included studies were conducted in Argentina,15 Australia,16 Brazil,1 17 Denmark,18 Finland,19 Germany,20–23 Hungary,8 24 25 Italy,9 26–31 Poland,14 Qatar,2 Russia,32 Serbia,33 Turkey,34 UK35 36 and USA 3 6 7 37–47. One study was a multicentre collaboration led by researchers in South Africa,48 and one study was conducted across different countries in Europe 49…”
Section: Resultsmentioning
confidence: 99%
“…Eleven (25%) studies included only male athletes,2 9 15 18 19 21 22 29 33 36 49 2 (5%) studies included only female athletes32 34 and 22 (51%) studies included both male and female athletes 1 3 6 8 14 16 24–28 35 37–39 41–44 46–48. Eight (19%) studies did not report data on sex 7 17 20 23 30 31 40 45. All studies included young adults, except one that included youth athletes (mean age 14.0±1.9) 27.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The training routine of athletes of collective sports was disrupted by COVID-19 more significantly than for those of individual sports, with their athletic performance more affected by the confinement than in individual sports, probably due to the added difficulty of having to meet with companions in order to train. Remarkably, an investigation on the repercussions of the COVID-19 pandemic on athletes through a cross-sectional study showed that athletes who had a teammate who tested positive were 15-fold more likely to be tested for COVID-19 [ 21 ].…”
Section: Discussionmentioning
confidence: 99%